The structure and transport properties of β-Mg3Bi2 in superionic conduction and molten phase - Akdere, Uensal; Guenay, Seckin D. (AMER INST PHYSICS, 2007)
Molecular dynamics simulation and Hypernetted-chain approximation of the liquids have been applied to obtained the static structure and transport properties of superionic beta-Mg3Bi2 at liquid phase near melting temperature. The potential used for the calculations has the same functional form that is originally used to investigate the fast-ion conduction phase of alpha-AgI. The system is still under investigation and should be concluded soon.
Keywords: Mg3Bi2; hypernetted-chain; molecular dynamics; superionic; Physics